Implementation of Character Education Through Civic Education Learning for Fourth Grade Students at SDN 7 Sambik Bangkol - Azri, Saepul; Taufik, M.; Jannah, Rauhun (International Journal of Education, Information Technology, and Others, 2025)
This study aims to describe the implementation of character education through Civic Education (PKn) learning in Grade IV students at SDN 7 Sambik Bangkol for the 2024/2025 academic year. The research questions include: (1) How is character education implemented through the Civic Education subject at SDN 7 Sambik Bangkol? and (2) What are the obstacles in the implementation of character education through the Civic Education subject at SDN 7 Sambik Bangkol? The research method used is descriptive qualitative with a qualitative approach. Data collection techniques include observation, interviews, and documentation. The research subjects consist of the school principal, Grade IV teacher, and students. The results of the study show that character education is integrated into Civic Education learning through various methods such as habituation, teacher role modeling, the insertion of character values into learning materials, and social activities such as communal work and mutual cooperation. The character values instilled include discipline, responsibility, cooperation, tolerance, and patriotism. Teachers play a major role as exemplary figures and the main facilitators in shaping students' character. However, the implementation of character education faces several obstacles, including differences in students' backgrounds that affect their acceptance of values, limited parental involvement in reinforcing character at home, and the negative influence of social media, which can undermine the moral values instilled at school. In addition, there are still teachers who do not fully understand the optimal approach and strategies for character-based learning. Therefore, synergy is needed between the school, teachers, parents, and the surrounding environment to support and strengthen the comprehensive and sustainable implementation of character education, particularly through the Civic Education subject.